Business Model Generation of Majalah EPIK - Marahakim, Sutansyah; Wandebori, Harimukti (Journal of Business and Management, 2012)
This final paper is made to generate a new business model for Majalah EPIK in order to increase its sales therefore creating sustainability. This model is based on Business model canvas by Osterwalder (2010) that consists of Customer Segment, Customer Relationship, Distribution Channel, Value Proposition, Key Activities, Key Resources, Key Partners, Revenue Stream, and Cost Structure. The Magazine is chosen because it is in urgent need for further development after and the detail of the problem has to be located based on internal and external point of view.The theoretical foundation used in this paper is mostly from Osterwalder’s Business Model Generation book, and the correlation of this business model with the actual condition of publishing business is based on the discussion and observation result of the team. the Business Model is broken down into aspects that considered being in need of customer’s point of view and those in need of in depth observation. The questionnaire spread is based on the aspects that needed customer point of view. The result from in depth observation shown that the magazine has to create a value proposition that can answer market needs without degrading the ideals of the team, such as the writings and layout design quality. Majalah EPIK has to hire clerical worker and attain capital, as their key resource and as its main revenue stream, the magazine should not hope for any profit from advertisement yet, but to maintain a sustained publishing period using money gained from sales. The cost structure that needed to be decreased is the consignment fee with distributors. Free distribution points or drop spots would be a solution, and can only be developed using partnering activities. The result from the descriptive research shown that two most important parts is the DistributionChannel and Key Partners. The magazine has to add more distribution channel and the amount of exemplar in each of the spot. The Key-Partnering activity has to consider benefits Majalah EPIK could get, especially to make free or at least low cost distribution points. The capital, whether acquired from investor or a bank loan, would be further used to print more exemplars of each edition, so it can cover wider area, therefore increasing the sales. Distribution channel does not only mean physical channels but also online publication. The website quality is still need to be further develop if the magazine wants to shift its positioning into a semi online publishing. Hopefully this new business model would create sustainability and then fame for MajalahEpik. Keywords:Majalah EPIK, Business Model Canvas, Magazine, Publishing, Media Busines.